Comunicação e consumo de música no ciberespaço: o papel do usuário de redes sociais na distribuição e compartilhamento de músicas - Abeche, Daniel Pala (2012)
The purpose of this Master Dissertation is to investigate the communicative relationship between users of cyberspace and the music files available on social networks and on distribution platforms and sharing sites, founded upon an analysis of the characteristics of cyberculture, digital communication and so-called free media, which provides the uncensored flow of content on the Web. The object of study are the users modes of appropriation and their objectives in using songs by others to make themselves visible, as well as the consequences of this for music producers and users in general. This visibility is grounded on recognition, power, reputation and the superimposition over others in pursuit of personal status. Today this motif corresponds to a phenomenon specific to the Web which has been little studied. The corpus of analysis consists of three music file sharing platforms, namely: blip.fm, last.fm and hypemachine.com. These platforms are considered major and innovative digital music content sharing networks. The observation and data collection involves an analysis of these tools and of the actions of individuals operating in them, as well as an extensive literature review and a critical assessment aimed at discovering the real objectives of users and possible consequences for them, for music, for its producers and for the music market. The research problem poses the following questions: How and to what extent does sharing and disseminating music in cyberspace, through the social networks that instigate user visibility, influence the functions of these participants and of the producers of these works? What is the real role played by users in these social networks and what are its consequences? Is the user aware of and complicit with this function or does he perform it imperceptibly? In answer to these questions, we propose the hypothesis that the user makes free use of music and disseminates it through these platforms, which are environments with high media visibility, achieving a higher status in these environments than the composer and producer of the work, which points to an inversion in the roles of value. The theoretical rationale is based on (a) studies about cyberculture and postmodernity, the phenomenon of media visibility, the search for recognition, and music; (b) on cultural studies, and (c) on theories that encompass digital media, social networks, cultural studies and the music market, and that provide the necessary epistemological references for the analysis of the object, with special focus on the following authors: Sfez Lucien, Jean Baudrillard, Axel Honneth, Eugenio Trivinho, Lucia Santaella, Paul Virilio, Andre Gorz and Krishan Kumar. Thus, we hope to contribute to the development of research on topics in the area of Communication and to studies that address the relationship between individuals and music in cyberspace